Thermochemical storage performances of methane reforming with carbon dioxide in tubular and semi-cavity reactors heated by a solar dish system. (1st January 2017) - Yu, Tao; Yuan, Qinyuan; Lu, Jianfeng; Ding, Jing; Lu, Yanling
Highlights: Tubular reactor heated by solar dish can perform thermochemical storage process. 3D flow and reaction model with unilateral concentrated solar flux was established. The simulated methane conversion and energy storage efficiency fit with experiments. Proper catalyst bed length exists for effects of residence time and reverse reaction. Semi-cavity reactor can increase methane conversion and energy storage efficiency. Abstract: Thermochemical storage performances of methane reforming with carbon dioxide in tubular and semi-cavity reactor heated by a solar dish system have been experimentally and numerically investigated. The methane conversion and thermochemical storage efficiency of methane reforming process in tubular reactor were experimentally studied for inlet flow rate 3–6 L/min and direct normal irradiation (DNI) 677.8–714.3 W/m 2 . According to the experimental system and results, Gaussian distribution model is derived for concentrated solar energy flux from solar dish, and a 3D finite volume method coupled with volumetric reaction kinetics and unilateral concentrated solar energy flux is established by experimental verification. The simulated methane conversion and energy storage efficiency have good agreements with the experimental data, and the temperature and species concentration distributions of the reactor are also successfully predicted. In the middle region of reactor, the concentrated solar energy flux and heat loss reach maxima, while the net heat flux and reaction kinetic rate reach maxima in the front region because of high temperature and high reactant fraction. As the catalyst bed length increases, the residence time and reverse reaction rate both rise, so there exists a proper catalyst bed length. When DNI rises, the methane reforming is promoted, while the heat loss remarkably increases, which results in the maximum thermochemical storage efficiency under proper DNI. Structural and operating parameters for the present tubular reactor can be further optimized, and the proper catalyst bed length is 300 mm, while the proper DNI is 250–300 W/m 2 (focal energy flux of 244.3–293.2 kW/m 2 ). A semi-cavity reactor is designed to reduce the heat loss and enhance the energy storage performance. According to the experimental results under inlet flow rate 2–6 L/min and DNI 452.4–598.5 W/m 2, the methane conversion of semi-cavity reactor can be increased to 74.8%, and the thermochemical storage efficiency and total energy efficiency can be respectively increased to 19.7% and 28.9%.